2010
DOI: 10.1590/s0100-06832010000100023
|View full text |Cite
|
Sign up to set email alerts
|

Preparo do solo em áreas de produção de grãos, silagem e pastejo: efeito na resistência tênsil e friabilidade de agregados

Abstract: RESUMOA compreensão e a quantificação do impacto do uso e manejo na qualidade do solo são fundamentais no desenvolvimento e seleção de sistemas de produção agrícola sustentáveis. O objetivo do presente estudo foi avaliar a qualidade estrutural de um Latossolo Bruno argiloso submetido a diferentes sistemas de produção e preparo do solo por meio da resistência tênsil (RT) e friabilidade (F) de agregados. O estudo foi realizado no município de Castro, Estado do Paraná, em três sistemas de produção e sete tipos de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
8
1
8

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 27 publications
5
8
1
8
Order By: Relevance
“…) when comparing the MA system with the TC system, while in the 10-20 cm layer the amount of lost CL decreased, the greatest loss being 0.61 g kg -1 from the MA system to the TC system, possibly more favorable to microbial activity and less protection of the CL inside smaller aggregates, similarly to results found by Bavoso et al (2010) and Ferreira et al (2011). A difference was found (p>0.05) in CL levels at the 0-5 cm and 5-10 cm depths between the MA system and the other systems (T5, T8, PA, TCP and TC).…”
Section: Agroforest System With Teak and Cocoa Tcsupporting
confidence: 76%
See 1 more Smart Citation
“…) when comparing the MA system with the TC system, while in the 10-20 cm layer the amount of lost CL decreased, the greatest loss being 0.61 g kg -1 from the MA system to the TC system, possibly more favorable to microbial activity and less protection of the CL inside smaller aggregates, similarly to results found by Bavoso et al (2010) and Ferreira et al (2011). A difference was found (p>0.05) in CL levels at the 0-5 cm and 5-10 cm depths between the MA system and the other systems (T5, T8, PA, TCP and TC).…”
Section: Agroforest System With Teak and Cocoa Tcsupporting
confidence: 76%
“…The difference found in the 10-20 cm layer between MA and TC regarding CL, according to Aguiar et al (2009), was probably due to the lack of grass species to help structure the soil. Bavoso et al (2010) concluded that different land use systems did to add significant values of MOS accumulation between the sampled systems, and results confirm and demonstrate that CL levels in the MOS are largely susceptible to the quality of soil management systems, enabling to check the short-and medium-term effect depending on the management being used (FABRIZZI et al, 2008, cited by CHAVEZ et al, 2009. …”
Section: Agroforest System With Teak and Cocoa Tcmentioning
confidence: 75%
“…One alternative to reduce the trampling impact would be to cut the forage and feed it to the animals in the trough, as in the ensiling and haying. However, the pressure on the soil, through heavy traffic and the agriculture machinery mass in order to cut the plants might also result in soil compaction (BAVOSO et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the faulty zones (pores) inside aggregates reduce, connecting the mineral particles or rearranging them, increasing the resistance of aggregates to breakage, and thus raising TS values. Bavoso et al (2010) observed that no-tillage provided larger TS values than other soil management systems. Tormena et al (2008b) verified that the cultivated areas had higher TS values than those of the fallow and the native forest.…”
Section: Resultsmentioning
confidence: 88%